A Systematic Review of Potential Therapeutic Use of Lycium Barbarum Polysaccharides in Disease. (12th February 2019) - Kwok, Sum Sum; Bu, Yashan; Lo, Amy Cheuk-Yin; Chan, Tommy Chung-Yan; So, Kwok Fai; Lai, Jimmy Shiu-Ming; Shih, Kendrick Co
Abstract : Objective. To evaluate the effect of Lycium barbarum polysaccharides in the treatment and/or prevention of diseases of different etiologies and systems. Methods. We performed an Entrez PubMed literature search using keywords "lycium", "barbarum", "polysaccharides", "anti-fibrotic", "anti-apoptotic", "anti-oxidizing", "anti-aging", "neuroprotection", "metabolism", "diabetes", "hyperlipidemia", "neuroprotection", and "immunomodulation" on the14 t h of August 2018, resulting in 207 papers, of which 20 were chosen after filtering for 'English language' and 'published within 10 years' as well as curation for relevance by the authors. Results. The 20 selected papers included 2 randomized control trials (1 double-blinded RCT and 1 double-blinded placebo-controlled RCT), 11 in vivo studies, 5 in vitro studies, 1 study with both in vivo and in vitro results, and 1 chemical study. There is good evidence from existing studies on the antifibrotic, antioxidizing, neuroprotective, anticancer, and anti-inflammatory effects of Lycium barbarum polysaccharides. However, there is a need for further studies in the form of large-scale clinical trials to support its use in humans. There is also significant potential for LBP as a safe and effective topical treatment in ocular surface diseases, owing to promising in vitro results and a lack of demonstrated toxic effects to corneal epithelial cells. Conclusion. Results from existing studies suggest that LBP is a promising therapeutic agent, particularly in the management of liver disease, hyperlipidemia, and diabetes. One major limitation of current research is a lack of standardization and quality control for the LBP used. The availability of research-grade LBP will inevitably promote future research in this field worldwide.